Sex in the wild: repeated observations of planktonic ciliate conjugation from field samples. (28th February 2022) - Romano, Filomena; Symiakaki, Katerina; Pitta, Paraskevi
Abstract: Ciliate conjugation is considered a rare event to encounter in the field and it is mostly reported from cultures. In this work, we describe a synchronized conjugation event of planktonic ciliates that was discovered twice; in September 2019, at two different locations in the Cretan Sea, Eastern Mediterranean, and in October 2020. In 2019, first, at 2 m depth of the coastal station POSEIDON-HCB, in samples fixed with acid Lugol and formaldehyde, we found 340 and 200 mating pairs L −1 of different ciliate species, respectively; and second, at the Heraklion port, we found 220 mating pairs L −1 of Strombidinopsis sp. and 1960 mating pairs L −1 of Strombidium sp. At the Heraklion port visited again in 2020, we found 800 mating pairs L −1 of Strombidinopsis sp. and 200 mating pairs L −1 of Strombidium sp. Since detailed descriptions of conjugation in pelagic oligotrich ciliates are missing, our observations indicate that ciliate conjugation could be a frequent and periodic phenomenon, under specific conditions.